2021
DOI: 10.1371/journal.pone.0246657
|View full text |Cite
|
Sign up to set email alerts
|

Alien plant species on roadsides of the northwestern Patagonian steppe (Argentina)

Abstract: The introduction of alien species represents one of the greatest threats to biodiversity worldwide. Highway construction increases the dispersal and invasion of exotic plant species. This study examined the assembly process of the plant communities to determine whether the roadsides of the Patagonian steppe represent a reservoir and dispersal source of invasive exotic species. We analyzed the composition of exotic and native species and functional groups present in the established vegetation and seed banks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 65 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…Our results suggest that the relative importance of the plant invasion–disturbance relationship in explaining invasion patterns decreases when the importance of abiotic factors, compared to that of biotic factors, increases. Consistently, it has been found that non‐native cover in the harsh conditions of the Patagonian steppe is higher in non‐disturbed than disturbed communities suggesting that roadside disturbance per seis not an important mechanism explaining plant invasion patterns in that region (Chichizola et al 2021) . Under stressful conditions, stress tolerant species, rather than ruderal species, should dominate the non‐native pool (Grime 1977, Pearson et al 2018).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Our results suggest that the relative importance of the plant invasion–disturbance relationship in explaining invasion patterns decreases when the importance of abiotic factors, compared to that of biotic factors, increases. Consistently, it has been found that non‐native cover in the harsh conditions of the Patagonian steppe is higher in non‐disturbed than disturbed communities suggesting that roadside disturbance per seis not an important mechanism explaining plant invasion patterns in that region (Chichizola et al 2021) . Under stressful conditions, stress tolerant species, rather than ruderal species, should dominate the non‐native pool (Grime 1977, Pearson et al 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Positive coefficients depict a positive effect on non-native species cover/richness, whereas negative coefficients depict a negative effect. disturbed communities suggesting that roadside disturbance per se is not an important mechanism explaining plant invasion patterns in that region (Chichizola et al 2021). Under stressful conditions, stress tolerant species, rather than ruderal species, should dominate the non-native pool (Grime 1977, Pearson et al 2018.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The richest species turned out to be complex families ( Asteraceae ), grasses ( Poaceae ) and legumes ( Fabaceae ). Many species belonging to Asteraceae and Poaceae produce high numbers of seeds adapted to wind dispersal (Chichizola et al, 2021), which can easily reach the surroundings. According to Kornaś and Medwecka-Kornaś (2002), habitats subjected to strong anthropogenic stresses are dominated by non-native species (anthropophytes).…”
Section: Resultsmentioning
confidence: 99%